Ending in Failure? The Performance of 'Takeover' Prime Ministers 1916–2016. Issue 4 (October 2016) - Worthy, Ben
Abstract: When Theresa May became Prime Minister in July 2016, she joined a list of eleven previous UK takeover leaders in the past 100 years. While the popular image is of Prime Ministers arriving in power after a general election victory, more than half of the Prime Ministers who governed since 1916 have acceded as 'takeover leaders' through an internal party process. This article analyses how such takeover leaders perform, concluding that May is likely to face greater obstacles and enjoy fewer advantages than if she had been popularly elected. Takeover leaders have less time in power and less chance of winning subsequent elections, and are generally rated as worse‐performing.